An empirical evaluation of a graphics creation technique for blind and visually impaired individuals. (September 2021) - Fernando, Sandra; Ohene-Djan, James
The representation of pictorial data by people who are blind and sight impaired has gathered momentum with research and development; however, little research has focused on the use of a screen layout to provide people who are blind and sight impaired users with the spatial orientation to create and reuse graphics. This article contributes an approach to navigating on the screen, manipulating computer graphics, and user-defined images. The technique described in this article enables features such as zooming, grouping, and drawing by calling primitive and user-defined shapes. It enables blind people to engage in and experience drawing and art production on their own. The navigation technique gives an initiative sense of autonomy with compass directions, makes it easy to learn, efficient to manipulate shape with a the simple drawing language, and takes less time to complete with system support features. An empirical evaluation was conducted to validate the suitability of the SETUP09 technique and to evaluate the accuracy, and efficiency of the navigation and drawing techniques proposed. The drawing experiment results confirmed high accuracy (88%) and efficiency among blind and visually impaired (BVI) users.